Correlation between the Computed Tomography Values of the Screw Path and Pedicle Screw Pullout Strength: An Experimental Study in Porcine Vertebrae - Ikeura, Atsushi (Asian Spine J, 2020)
STUDY DESIGN: Biomechanical study. PURPOSE: To assess the correlation between the computed tomography (CT) values of the pedicle screw path and screw pull-out strength. OVERVIEW OF LITERATURE: The correlation between pedicle screw pull-out strength and bone mineral density has been well established. In addition, several reports have demonstrated a correlation between bone mineral density and CT values. However, no previous biomechanical studies investigated the correlation between CT values and pedicle screw pull-out strength. METHODS: Sixty fresh-frozen lumbar vertebrae from 6-month-old pigs were used. Before screw insertion, the CT values of the screw path were obtained for each sample. Specimens were then randomly divided into three equal groups. Each group had one of three pedicle screws inserted: 4.0-mm LEGACY (4.0-LEG), 4.5-mm LEGACY (4.5-LEG), or 4.5-mm SOLERA (4.5-SOL) (all from Medtronic Sofamor Danek Inc., Memphis, TN, USA). Each screw had a consistent 30-mm thread length. Axial pull-out testing was performed at a rate of 1.0 mm/min. Correlations between the CT values and pedicle screw pull-out strength were evaluated using Pearson’s correlation coefficient analysis. RESULTS: The correlation coefficients between the CT values of the screw path and pedicle screw pull-out strength for the 4.0-LEG, 4.5-LEG, and 4.5-SOL groups were 0.836 (p<0.001), 0.780 (p<0.001), and 0.873 (p<0.001), respectively. Greater CT values were associated with greater screw pull-out strength. CONCLUSIONS: The CT values of the screw path were strongly positively correlated with pedicle screw pull-out strength, regardless of the screw type and diameter, suggesting that the CT values could be clinically useful for predicting pedicle screw pull-out strength.